Formulasi Masker Gel Peel-Off Ekstrak Buah Naga (Hylocereus Polyrhizus) dan Ekstrak Daun Pepaya dengan Penambahan Gelatin sebagai Gelling Agent - Niat Hati Dachi; Herawati Oktavianty; Ida Bagus Banyuro Partha (Program Studi Teknologi Hasil Pertanian, 2024)
A peel-off gel face mask is a type of face mask that comes in a gel form, which can be applied to the face, dries, and can be directly peeled off from the skin. This research aims to determine the difference between the peel-off gel mask’s gelatin-based active ingredients that have anti-bacterial and anti-inflammation properties from staphylococcus aureus. The research design used in this study is a Complete Block Design with 2 factors, namely the comparison of dragon fruit extract and papaya leaf extract with the addition of gelatin. Factor 1 comparison of dragon fruit extract and papaya leaf extract (A1 = 80: 20%, A2 = 70: 30%, A3 = 60: 40%), factor 2 addition of gelatin (B1 = 1.5%, B2 = 2%, B3 = 2.5%). The analysis carried out on peel-off gel masks is physical and chemical properties, as well as organoleptic tests. The research results indicate that the difference in concentrations of dragon fruit extract and papaya leaf extract with the addition of gelatin has a significant effect on antioxidant activity, viscosity, adhesive time, drying time, antibacterial inhibition, and organoleptic testing. Based on the results of the physical and chemical tests of the peel-off gel mask, the recommended antioxidant activity is sample A1B1 (69.58%), and the sample with the highest antibacterial inhibition is sample A3B3 (13.50 mm).